Modified sugarcane activated carbon electrode material and preparation method and application thereof
By building a mesh frame on the surface of the sugarcane activated carbon electrode and modifying the sugarcane activated carbon electrode material, the problems of low oxygen utilization efficiency and high energy consumption in the electrofenton method are solved, and efficient pollutant degradation and energy consumption reduction are achieved.
Patent Information
- Application Number
- CN202411509009.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In the electrofenton method, the low oxygen utilization efficiency and high energy consumption of oxygen are the biggest obstacles to practical application, and the existing technology has not effectively solved this problem.
By building a mesh frame on the surface of the sugarcane activated carbon electrode, the sugarcane activated carbon electrode material is modified to improve oxygen utilization and realize an electrofenton system without aeration.
The modified sugarcane activated carbon electrode material significantly improves oxygen utilization, reduces energy consumption, and has good degradation effect on the pollutant pronelol, with a removal rate greater than 90%.
Smart Images

Figure CN119430400A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a modified sugarcane activated carbon electrode material and a preparation method and application thereof. Background Art
[0002] Electro-Fenton (EF) is an advanced oxidation process. Its principle is mainly based on the Fenton method, that is, the reaction system contains both Fe 2+ When reacting with H2O2, it can produce ·OH (oxidation potential is 2.8 V) with extremely strong oxidizing ability, which is used to degrade organic pollutants. The electro-Fenton method overcomes some limitations of the Fenton method, such as the need to add Fe 2+ Salt and H2O2, while H2O2 is generated in situ in the electro-Fenton process, thus avoiding the transportation and storage problems of H2O2 in the Fenton process. 2+ Similar electroregeneration was also performed at the cathode, reducing the initial dose of Fe 2+ dosage, almost eliminating the production of iron slag.
[0003] Since the electro-Fenton process uses oxygen to produce H2O2 in situ at the cathode, the efficiency of the electro-Fenton process depends largely on the performance of the cathode, as it determines the production of H2O2. In addition, the low concentration of dissolved oxygen in water requires an aeration device, which also causes aeration to consume more than 95% of the electrical energy. Therefore, low oxygen utilization efficiency and high energy consumption are the biggest obstacles to the practical application of the electro-Fenton process.
[0004] Traditional carbonaceous materials such as carbon fiber, carbon sponge, carbon felt and mesh glassy carbon have been widely reported to be used to prepare electrode materials. For example: Reference (Shi Shen et al., Selection of cathode electro-Fenton electrode materials and research on treatment of printing and dyeing wastewater, Ordnance Materials Science and Engineering, 2014, 37: 115-117) uses an electro-Fenton reactor with activated carbon fiber cathode material to study the relevant factors affecting the treatment of printing and dyeing wastewater. Reference (Chen Ma Yu et al., Research on electro-Fenton degradation of methyl orange by carbon felt electrode, Applied Chemical Industry, 2020, 49: 143-146) studied the degradation of methyl orange by electro-Fenton of azo dye wastewater by carbon felt electrode. Reference (Chen Cong, Research on the efficiency of pretreatment of printing and dyeing wastewater by new nickel electrode electro-Fenton method, Master's thesis of Harbin Institute of Technology, 2015) uses an electro-Fenton system with graphite plate as anode and nickel foam as cathode to treat actual wastewater. However, none of these documents solves the technical problems of low oxygen utilization efficiency and high energy consumption in the electro-Fenton method. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a modified sugarcane activated carbon electrode material. The method uses sugarcane to prepare an activated carbon electrode and constructs a mesh frame with oxygen capture function on the surface of the activated carbon electrode, thereby improving oxygen utilization and realizing an electro-Fenton system without aeration. The experimental results show that the degradation effect of the pollutant propranolol is good. Another object of the present invention is to provide a modified sugarcane activated carbon electrode material prepared by the above method.
[0006] Another object of the present invention is to provide an application of the modified sugarcane activated carbon electrode material.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a modified sugarcane activated carbon electrode material comprises the following steps: (1) Pre-treating, calcining, activating and grinding fresh sugarcane or bagasse after juice extraction to obtain carbon powder; (2) Add carbon powder to anhydrous ethanol, then add polytetrafluoroethylene, heat and stir until a gel appears, to prepare activated carbon gel; (3) coating the activated carbon gel on the surface of nickel foam, drying, pressing with a tablet press, and then calcining to obtain a sugarcane activated carbon electrode; (4) Plronic F127 (block polyether F-127), CoCl3·6H2O (cobalt trichloride hexahydrate) and CH3COOH were dissolved in water and stirred to obtain a mixed solution; sugarcane activated carbon electrode (SC) and NH2-BDC (2-aminoterephthalic acid) were added to the mixed solution, stirred for a period of time, and then subjected to hydrothermal reaction to obtain modified sugarcane activated carbon electrode material (SC-RF for short).
[0008] The specific steps of step (1) include: peeling the sugarcane, cutting it into segments, drying it, or drying the bagasse after squeezing the juice, then using water and ethanol to ultrasonically clean the sugarcane to remove the residual substances in the sugarcane, and then thoroughly cleaning and drying it; then calcining and carbonizing the dried sugarcane at 800-1000 °C for 5 h under the protection of inert gas; activating the carbonized sugarcane at 700-800 °C for 10 h under CO2 atmosphere, and grinding the activated sugarcane into carbon powder. Experiments show that the electrode prepared by carbonizing in a nitrogen atmosphere at 900 °C and then activating it in a CO2 atmosphere at 750 °C has the best performance.
[0009] The average adsorption pore diameter of the carbon powder is 2.05 nm.
[0010] The heating temperature in step (2) is 80°C.
[0011] In step (2), the mass ratio of carbon powder to polytetrafluoroethylene is 8:1, and the volume ratio of anhydrous ethanol to polytetrafluoroethylene is 20:2.
[0012] The drying temperature in step (3) is 60°C; the calcination refers to calcination at 360°C for 1 h under the protection of inert gas.
[0013] The loading amount of activated carbon on the nickel foam surface in step (3) is 0.05 g / cm 2 .
[0014] The size of the nickel foam in step (3) is 2 cm×2 cm.
[0015] The tablet press in step (3) has a pressing pressure of 4 MPa.
[0016] The amounts of Plronic F127, CoCl3·6H2O, CH3COOH and NH2-BDC used in step (4) are 360 parts by mass, 400 parts by mass, 0.6 parts by volume and 136 parts by mass, respectively. In the present invention, 1 part by mass: 1 part by volume = 1 mg / mL.
[0017] The hydrothermal reaction in step (4) refers to heating at 110°C for 24 h.
[0018] The present invention also provides an application of the modified sugarcane activated carbon electrode material prepared above, wherein the modified sugarcane activated carbon electrode material can be used to degrade non-steroidal drugs (such as propranolol) in wastewater.
[0019] The specific steps of the application include: using a ruthenium-iridium electrode as an anode and a modified sugarcane activated carbon electrode material (SC-RF) as a cathode, fixing the anode and the cathode in a penetration reactor with a distance of 1 cm between the two electrodes; adding supporting electrolytes Na2SO4 and FeSO4 to wastewater to be degraded containing non-steroidal drugs, and adjusting the pH to 3 with H2SO4 to obtain a reaction solution; pumping the reaction solution into the penetration reactor by a peristaltic pump to obtain an electro-Fenton system, and then applying electricity for degradation.
[0020] The non-steroidal drug in the wastewater to be degraded is propranolol, and its initial concentration is 10 mg / L; the stirring speed is 500 rpm.
[0021] During the above degradation process, samples were taken to determine the concentration of propranolol and the removal rate of propranolol was calculated. The removal rate of propranolol was greater than 90%.
[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The cathode material prepared by constructing a mesh frame on the surface of a sugarcane activated carbon electrode in the present invention has a higher ability to capture O2 than the unmodified electrode, thereby producing more H2O2 and hydroxyl radicals, which can improve the electrochemical properties and has a good degradation effect on propranolol in pollutants.
[0023] 2. The modified sugarcane activated carbon electrode material prepared by the present invention has a higher oxygen utilization rate compared with other activated carbon electrodes, and has a higher degradation efficiency for pollutants without aeration, thus solving the problem of high energy consumption caused by the aeration device in the electro-Fenton process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 1 is an electron microscope image of the unactivated and activated carbon powders prepared in Example 1.
[0025] Figure 2 It is the linear sweep voltammogram of the SC electrode and SC-RF electrode materials prepared in Example 1.
[0026] Figure 3 The SC electrode and SC-RF electrode materials prepared in Example 1 are used to degrade propranolol.
[0027] Figure 4 It is a comparison chart of the SC-RF electrode material prepared in Example 1 and the CNTs-RF electrode material prepared in Comparative Example 1 for degrading propranolol.
[0028] Figure 5 It is a comparison chart of the SC-RF electrode material prepared in Example 1 and the HMC-RF electrode material prepared in Comparative Example 2 for the degradation of propranolol. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.
[0030] Example 1 This embodiment is a method for preparing and modifying sugarcane activated carbon electrode materials, which is: (1) Peel the sugarcane and cut it into pieces, then dry it at 60 °C to remove moisture. Use deionized water and ethanol to ultrasonically clean the dried sugarcane to remove residual substances in the sugarcane, and then thoroughly clean and dry it. Calcining and carbonizing the dried sugarcane at 900 °C in a N2 atmosphere for 5 h; Activating the carbonized sugarcane at 750 °C in a CO2 atmosphere for 10 h, and grinding the activated sugarcane into carbon powder; (2) Add the obtained carbon powder to 20 mL of anhydrous ethanol, then add 2 mL of polytetrafluoroethylene, heat in a water bath at 80 °C, and stir until a gel appears to obtain activated carbon gel. The mass ratio of carbon powder to polytetrafluoroethylene is 8:1. (3) The nickel foam was cut into 2 cm × 2 cm sizes, and the cut nickel foam was cleaned with acetone and ultrasonicated for 20 min. The cleaned nickel foam was rinsed with deionized water and dried at 60 °C for later use. The obtained activated carbon gel was evenly coated on the surface of the nickel foam (the loading amount of activated carbon was 0.05 g / cm 2 ), the coated nickel foam was placed in an oven at 60 °C and dried overnight; the dried nickel foam was pressed using a tablet press (pressure was 4 MPa), and the pressed nickel foam was calcined at 360 °C for 1 h in a N2 atmosphere to obtain a SC electrode.
[0031] (4) The obtained SC electrode was soaked in acetone for 30 minutes for ultrasonic treatment to remove impurities and oil stains, and then rinsed thoroughly with deionized water. Plronic F127 (360 mg), CoCl3·6H2O (400 mg), and CH3COOH (0.6 mL) were dissolved in 30 mL of deionized water and stirred for 1 hour to obtain a mixed solution. Subsequently, a cleaned SC electrode (size 2 cm×2 cm) and 136 mg NH2-BDC were added to the above mixed solution and stirred for another 2 h. The obtained mixture was sealed in a stainless steel autoclave lined with polytetrafluoroethylene and heated at 110 °C for 24 h to obtain a SC-RF electrode. After cooling to room temperature, the SC-RF electrode was washed with ethanol 5 times and dried in a vacuum oven at 80 °C overnight.
[0032] Figure 1 (a) is a SEM image of unactivated sugarcane charcoal powder (the cleaned and dried sugarcane blocks in Example 1 were calcined at 900°C and then ground into powder). It can be seen that the surface is smooth and there are regular pores on the surface of the activated carbon. Figure 1 (b) is the SEM image of the activated sugarcane activated carbon powder. It can be clearly seen that the pore size after activation is larger than that of the unactivated one. Figure 2 LSV diagrams of SC electrode and SC-RF electrode.
[0033] The SC electrode and SC-RF electrode prepared in Example 1 were used as cathodes to degrade propranolol. The experimental conditions were as follows: 200 mL of 10 mg / L propranolol hydrochloride aqueous solution was measured, 1.42 g of Na2SO4 electrolyte and 0.0278 g of FeSO4 were added, pH=3 was adjusted with 1 mol / L H2SO4, and the mixture was poured into an electrolytic cell to obtain a reaction solution. The reaction solution was pumped into a peristaltic pump into a penetration reactor. SC and SC-RF were used as cathodes, and ruthenium-iridium electrodes of the same size were fixed as anodes in the penetration reactor. A double-electrode system was used with a constant current density of 10 mA / cm 2 , magnetic stirring rate of 500 r / min, and electrical degradation for 30 min at room temperature.
[0034] like Figure 3 As shown, the degradation rates of propranolol by the SC electrode (the sugarcane activated carbon electrode pressed from the activated sugarcane activated carbon powder in Example 1) and the SC-RF electrode (the electrode after the hydrothermal method was used to construct a mesh frame on the surface of the SC electrode in Example 1) were 62.9% and 90.1% respectively in 30 minutes. It can be seen that the modified electrode is better than the unmodified electrode and the degradation rate of the modified electrode is faster. This is because the modified electrode is easier to capture dissolved oxygen from water, so that the production of H2O2 is higher at the same time, and more hydroxyl radicals are generated, which also degrades propranolol faster.
[0035] Comparative Example 1 In this comparative example, multi-walled carbon nanotubes are used to replace sugarcane activated carbon to prepare a multi-walled carbon nanotube modified electrode (CNTs-RF), and the preparation steps are as follows: (1) Add multi-walled carbon nanotube powder to 20 mL of anhydrous ethanol, then add 2 mL of polytetrafluoroethylene and heat in a water bath at 80 °C, stirring until a gel appears to obtain a multi-walled carbon nanotube gel. The mass ratio of multi-walled carbon nanotube powder to polytetrafluoroethylene is 8:1. (2) The nickel foam was cut into 2 cm × 2 cm sizes, and the cut nickel foam was cleaned with acetone and ultrasonicated for 20 min. The cleaned nickel foam was rinsed with deionized water and dried at 60 °C for later use. The obtained multi-walled carbon nanotube gel was evenly coated on the surface of the nickel foam (the loading amount of multi-walled carbon nanotubes was 0.05 g / cm 2 ), the coated nickel foam was placed in an oven at 60°C and dried overnight; the dried nickel foam was pressed using a tablet press, and the pressed nickel foam was calcined at 360°C for 1 h in a N2 atmosphere to obtain an electrode.
[0036] (3) The obtained electrode was soaked in acetone for 30 minutes for ultrasonic treatment to remove impurities and oil stains, and then rinsed thoroughly with deionized water. Plronic F127 (360 mg), CoCl3·6H2O (400 mg), and CH3COOH (0.6 mL) were dissolved in 30 mL of deionized water and stirred for 1 hour. Subsequently, a cleaned electrode (size 2 cm×2 cm) and 136 mg NH2-BDC were added to the above solution and stirred for another 2 h. The resulting mixture was sealed in a stainless steel autoclave lined with polytetrafluoroethylene and heated at 110 °C for 24 h to prepare a CNTs-RF electrode. After cooling to room temperature, the CNTs-RF electrode was washed with ethanol 5 times and dried in a vacuum oven at 80 °C overnight.
[0037] Figure 4 This is a comparison chart of the degradation effects of the SC-RF electrode and the CNTs-RF electrode prepared in Example 1 on propranolol under the same conditions. The degradation experimental conditions are the same as in Example 1. It can be clearly seen from the figure that the degradation effect of the SC-RF electrode is better than that of the CNTs-RF electrode.
[0038] Comparative Example 2 This comparative example adopts a sugarcane activated carbon electrode (HMC-RF) prepared by a different process, and the preparation method is as follows: (1) Peel fresh sugarcane and cut it into segments and dry it at 60 °C. Use deionized water and ethanol to ultrasonically clean the dried sugarcane blocks to remove residual substances in the sugarcane, thoroughly clean them and dry them. Grind the dried sugarcane into powder, add sugarcane powder (6.0 g) and ultrapure water (60 mL) into a Teflon-lined hydrothermal reactor and stir for 30 min. Then place the reactor in an oven and heat it at 200 °C for 24 h to hydrolyze the unstable components in the biomass and obtain hydrogen carbon (HC) with a widened pore structure.
[0039] (2) After filtration and drying, the hydrogen carbon and zinc chloride activator were mixed in a mass ratio of 1:3. The uniform mixture was then heated at 800 °C (heating rate of 5 °C min -1 ) was calcined in a tube furnace under N2 atmosphere for 1 hour. After cooling, it was washed several times with 1 mol / L HCl solution and ultrapure water to remove residual impurities, and then dried in a vacuum oven at 80 °C overnight to obtain biochar, named HMC; (3) Add HMC powder to 20 mL of anhydrous ethanol, then add 2 mL of polytetrafluoroethylene, heat in a water bath at 80 °C, and stir until a gel appears to obtain activated carbon gel. The mass ratio of HMC powder to polytetrafluoroethylene is 8:1. (4) The nickel foam was cut into 2 cm × 2 cm sizes, and the cut nickel foam was cleaned with acetone and ultrasonicated for 20 min. The cleaned nickel foam was rinsed with deionized water and dried at 60 °C for later use. The obtained activated carbon gel was evenly coated on the surface of the nickel foam (the loading amount of activated carbon was 0.05 g / cm 2 ), the coated nickel foam was placed in an oven at 60 °C and dried overnight; the dried nickel foam was pressed using a tablet press, and the pressed nickel foam was calcined at 360 °C for 1 h in a N2 atmosphere to obtain an HMC electrode.
[0040] (5) The obtained HMC electrode was soaked in acetone for 30 minutes for ultrasonic treatment to remove impurities and oil stains, and then rinsed thoroughly with deionized water. Plronic F127 (360 mg), CoCl3·6H2O (400 mg), and CH3COOH (0.6 mL) were dissolved in 30 mL of deionized water and stirred for 1 hour. Subsequently, a cleaned electrode (size 2 cm×2 cm) and 136 mg NH2-BDC were added to the above solution and stirred for another 2 h. The resulting mixture was sealed in a stainless steel autoclave lined with polytetrafluoroethylene and heated at 110°C for 24 h to obtain an HMC-RF electrode. After cooling to room temperature, the HMC-RF electrode was washed 5 times with ethanol and dried in a vacuum oven at 80°C overnight.
[0041] Figure 5 This is a comparison chart of the degradation effects of the SC-RF electrode and the HMC-RF electrode prepared in Example 1 on propranolol under the same conditions. The degradation experimental conditions are the same as in Example 1. It can be clearly seen from the figure that the degradation effect of the SC-RF electrode is better than that of the HMC-RF electrode.
[0042] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a modified sugarcane activated carbon electrode material, characterized in that: The following steps are involved: (1) Pre-treating, calcining, activating and grinding fresh sugarcane or sugarcane bagasse after juice extraction to obtain carbon powder; the activation refers to activating the carbonized sugarcane at 700-800 °C for 10 h under a CO2 atmosphere; (2) Add carbon powder to anhydrous ethanol, then add polytetrafluoroethylene, heat and stir until a gel appears, to prepare activated carbon gel; (3) coating the activated carbon gel on the surface of nickel foam, drying, pressing with a tablet press, and then calcining to obtain a sugarcane activated carbon electrode; (4) Plronic F127, CoCl3·6H2O and CH3COOH were dissolved in water and stirred to obtain a mixed solution; a sugarcane activated carbon electrode and 2-aminoterephthalic acid were added to the mixed solution, stirred, and then subjected to a hydrothermal reaction to obtain a modified sugarcane activated carbon electrode material.
2. The method according to claim 1, characterized in that The specific steps of step (1) include: peeling the sugarcane, cutting it into segments and drying it, or drying the sugarcane bagasse after squeezing the juice, then using water and ethanol to ultrasonically clean the sugarcane to remove residual substances in the sugarcane, and then thoroughly cleaning and drying it; then calcining and carbonizing the dried sugarcane at 800-1000°C for 5 hours under the protection of inert gas; activating the carbonized sugarcane at 700-800°C for 10 hours under a CO2 atmosphere, and grinding the activated sugarcane into carbon powder.
3. The method according to claim 1, characterized in that The heating temperature in step (2) is 80°C.
4. The method according to claim 1, wherein in step (2), the mass ratio of the carbon powder to polytetrafluoroethylene is 8:1, and the volume ratio of anhydrous ethanol to polytetrafluoroethylene is 20:
2.
5. The method according to claim 1, characterized in that The drying temperature in step (3) is 60°C; the calcination refers to calcination at 360°C for 1 h under the protection of inert gas; The loading amount of activated carbon on the nickel foam surface in step (3) is 0.05 g / cm 2 .
6. The method according to claim 1, characterized in that The pressing pressure of the tablet press in step (3) is 4 MPa; the size of the nickel foam in step (3) is 2 cm×2 cm.
7. The method according to claim 1, characterized in that The amounts of Plronic F127, CoCl3·6H2O, CH3COOH and 2-aminoterephthalic acid used in step (4) are 360 parts by mass, 400 parts by mass, 0.6 parts by volume and 136 parts by mass, respectively.
8. The method according to claim 1, characterized in that The hydrothermal reaction in step (4) refers to heating at 110°C for 24 h.
9. A modified sugarcane activated carbon electrode material prepared by the method according to any one of claims 1 to 8.
10. The use of the modified sugarcane activated carbon electrode material according to claim 9, characterized in that: The modified sugarcane activated carbon electrode material is used for degrading non-steroidal drugs in wastewater.
Citation Information
Patent Citations
Preparation method and application of environment-friendly electro-Fenton negative electrode
CN110117046A
Preparation method of graphite felt loaded metal organic framework compound cathode material and application thereof
CN111392821A